Secure Group Association Management in Heterogeneous Distributed Sensor Networks - Pathan, Al-Sakib Khan; Hong, Choong Seon (IEEE Seoul Section, 2008)
A Heterogeneous Distributed Sensor Network (HDSN) is a type of distributed sensor network where sensors with different functional types participate at the same time. In this network model, the sensors are associated with different deployment groups but they cooperate with each other within and out of their respective groups. The heterogeneity of HDSN refers to the functional heterogeneity of the sensors participating in the network unlike the heterogeneity considered (e.g., considering transmission range, energy level, computation ability, sensing range) for traditional heterogeneous sensor networks. Taking this model into account, we propose a secure group association authentication mechanism using one-way accumulator which ensures that; before collaborating for a particular task, any pair of nodes in the same deployment group can verify the legitimacy of group association of each other. Secure addition and deletion of sensors are also supported in this approach. In addition, a policy-based sensor addition procedure is also suggested. For secure handling of disconnected node of a group, we use an efficient pairwise key derivation scheme. Side by side proposing our mechanisms, we also discuss the characteristics of HDSN, its scopes, applicability, challenges, and future. The efficiency of our management approach is demonstrated with performance evaluation and analysis.